The natural killer cell response to West Nile virus in young and old individuals with or without a prior history of infection - Yao, Yi; Strauss-Albee, Dara M.; Zhou, Julian Q.; Malawista, Anna; Garcia, Melissa N.; Murray, Kristy O.; Blish, Catherine A.; Montgomery, Ruth R. (PloS one, 2017)
West Nile virus (WNV) typically leads to asymptomatic infection but can cause severe neuroinvasive disease or death, particularly in the elderly. Innate NK cells play a critical role in antiviral defenses, yet their role in human WNV infection is poorly defined. Here we demonstrate that NK cells mount a robust, polyfunctional response to WNV characterized by cytolytic activity, cytokine and chemokine secretion. This is associated with downregulation of activating NK cell receptors and upregulation of NK cell activating ligands for NKG2D. The NK cell response did not differ between young and old WNV-naïve subjects, but a history of symptomatic infection is associated with more IFN-γ producing NK cell subsets and a significant decline in a specific NK cell subset. This NK repertoire skewing could either contribute to or follow heightened immune pathogenesis from WNV infection, and suggests that NK cells could play an important role in WNV infection in humans.